Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let [tex]\( a = \frac{3+\sqrt{2}}{3-\sqrt{2}} \)[/tex] and [tex]\( b = \frac{3-\sqrt{2}}{3+\sqrt{2}} \)[/tex].
To find the sum [tex]\( a + b \)[/tex], we first rationalize the denominators of the fractions for both [tex]\( a \)[/tex] and [tex]\( b \)[/tex].
### Rationalizing [tex]\( a \)[/tex]:
[tex]\[ a = \frac{3 + \sqrt{2}}{3 - \sqrt{2}} \][/tex]
Multiply the numerator and the denominator by the conjugate of the denominator, [tex]\( 3 + \sqrt{2} \)[/tex]:
[tex]\[ a = \frac{(3 + \sqrt{2})(3 + \sqrt{2})}{(3 - \sqrt{2})(3 + \sqrt{2})} \][/tex]
Simplify the numerator and the denominator:
[tex]\[ = \frac{9 + 6\sqrt{2} + 2}{9 - 2} \][/tex]
[tex]\[ = \frac{11 + 6\sqrt{2}}{7} \][/tex]
### Rationalizing [tex]\( b \)[/tex]:
[tex]\[ b = \frac{3 - \sqrt{2}}{3 + \sqrt{2}} \][/tex]
Similarly, multiply the numerator and the denominator by the conjugate of the denominator, [tex]\( 3 - \sqrt{2} \)[/tex]:
[tex]\[ b = \frac{(3 - \sqrt{2})(3 - \sqrt{2})}{(3 + \sqrt{2})(3 - \sqrt{2})} \][/tex]
Simplify the numerator and the denominator:
[tex]\[ = \frac{9 - 6\sqrt{2} + 2}{9 - 2} \][/tex]
[tex]\[ = \frac{11 - 6\sqrt{2}}{7} \][/tex]
### Finding [tex]\( a + b \)[/tex]:
[tex]\[ a + b = \frac{11 + 6\sqrt{2}}{7} + \frac{11 - 6\sqrt{2}}{7} \][/tex]
Combine the fractions:
[tex]\[ = \frac{(11 + 6\sqrt{2}) + (11 - 6\sqrt{2})}{7} \][/tex]
Simplify the expression inside the numerator:
[tex]\[ = \frac{11 + 11}{7} \][/tex]
[tex]\[ = \frac{22}{7} \][/tex]
Thus,
[tex]\[ a + b = \frac{22}{7} \][/tex]
The value of [tex]\( \frac{22}{7} \)[/tex] is approximately [tex]\( 3.142857142857143 \)[/tex].
Therefore, the value of [tex]\( a + b \)[/tex] is:
[tex]\[ \boxed{3.142857142857143} \][/tex]
To find the sum [tex]\( a + b \)[/tex], we first rationalize the denominators of the fractions for both [tex]\( a \)[/tex] and [tex]\( b \)[/tex].
### Rationalizing [tex]\( a \)[/tex]:
[tex]\[ a = \frac{3 + \sqrt{2}}{3 - \sqrt{2}} \][/tex]
Multiply the numerator and the denominator by the conjugate of the denominator, [tex]\( 3 + \sqrt{2} \)[/tex]:
[tex]\[ a = \frac{(3 + \sqrt{2})(3 + \sqrt{2})}{(3 - \sqrt{2})(3 + \sqrt{2})} \][/tex]
Simplify the numerator and the denominator:
[tex]\[ = \frac{9 + 6\sqrt{2} + 2}{9 - 2} \][/tex]
[tex]\[ = \frac{11 + 6\sqrt{2}}{7} \][/tex]
### Rationalizing [tex]\( b \)[/tex]:
[tex]\[ b = \frac{3 - \sqrt{2}}{3 + \sqrt{2}} \][/tex]
Similarly, multiply the numerator and the denominator by the conjugate of the denominator, [tex]\( 3 - \sqrt{2} \)[/tex]:
[tex]\[ b = \frac{(3 - \sqrt{2})(3 - \sqrt{2})}{(3 + \sqrt{2})(3 - \sqrt{2})} \][/tex]
Simplify the numerator and the denominator:
[tex]\[ = \frac{9 - 6\sqrt{2} + 2}{9 - 2} \][/tex]
[tex]\[ = \frac{11 - 6\sqrt{2}}{7} \][/tex]
### Finding [tex]\( a + b \)[/tex]:
[tex]\[ a + b = \frac{11 + 6\sqrt{2}}{7} + \frac{11 - 6\sqrt{2}}{7} \][/tex]
Combine the fractions:
[tex]\[ = \frac{(11 + 6\sqrt{2}) + (11 - 6\sqrt{2})}{7} \][/tex]
Simplify the expression inside the numerator:
[tex]\[ = \frac{11 + 11}{7} \][/tex]
[tex]\[ = \frac{22}{7} \][/tex]
Thus,
[tex]\[ a + b = \frac{22}{7} \][/tex]
The value of [tex]\( \frac{22}{7} \)[/tex] is approximately [tex]\( 3.142857142857143 \)[/tex].
Therefore, the value of [tex]\( a + b \)[/tex] is:
[tex]\[ \boxed{3.142857142857143} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.